Examining the association between early life social adversity and BMI changes in childhood: a life course trajectory analysis. Issue 4 (25th August 2015) - Morris, T. T.; Northstone, K.; Howe, L. D.
Summary: Background: A number of studies have found associations between multiple aspects of social adversity and obesity in childhood, yet this research has largely been limited to cross‐sectional data. Objectives: This study aimed to address this limitation by using life course trajectory methods to determine whether multiple aspects of social adversity in early childhood are associated with changes in body mass index (BMI) throughout childhood. Methods: Associations between multiple measures of social adversity from birth to 4 years and subsequent BMI trajectories to age 17 were examined in 7021 children in the Avon Longitudinal Study of Parents and Children. Results: Higher BMI throughout ages 12–17 were observed for children whose parents had separated, were exposed to frequent residential mobility or who experienced moderate or great household financial difficulty in early childhood. After adjustment for confounding variables, associations were attenuated but remained for both moderate (two moves) and high (≥3 moves) residential mobility (mean % difference in BMI at age 17 for children experiencing moderate and high residential mobility before age 4 compared with those experiencing no moves: 2.3; 95% CI: 0.5–4.2; P = 0.015 and 4.2; 95% CI: 1.4–7.0; P = 0.004, respectively). Conclusions: Associations between BMI and social adversity in childhood are present but largely explained by background socioeconomic position. However, there remain small but important differences between the BMI of children who are exposed to frequent residential mobility in early childhood after adjustment for socioeconomic and other confounders.